2012
DOI: 10.1159/000341259
|View full text |Cite
|
Sign up to set email alerts
|

Complete Response after Short-Term Sorafenib Treatment in a Patient with Lymph Node Metastasis of Hepatocellular Carcinoma

Abstract: A 60-year-old man received interferon/ribavirin combination therapy for chronic hepatitis C in 2002 and achieved sustained virological response. In 2008, a hepatocellular carcinoma (HCC) with a diameter of 60 mm appeared and surgical resection was performed. In March 2011, the patient was referred to our hospital because of portal lymph node swelling. Abdominal ultrasonography, dynamic CT and dynamic MRI did not show any tumors in the liver, but revealed portal lymph node swelling (18 × 11 mm). Taking the elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…In addition, our case demonstrated a significant decreasing linear trend after log transformation. Some studies have also reported a rapid decrease in AFP levels, but this characteristic was not further analyzed 711,1315. In the current case, the calculated half-life of AFP level was 6.84 days, which was similar to that reported in the previous studies 711,1315.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, our case demonstrated a significant decreasing linear trend after log transformation. Some studies have also reported a rapid decrease in AFP levels, but this characteristic was not further analyzed 711,1315. In the current case, the calculated half-life of AFP level was 6.84 days, which was similar to that reported in the previous studies 711,1315.…”
Section: Discussionsupporting
confidence: 79%
“…This indicates that sorafenib is effective in some HCC patients despite a low-dose administration. In some patients, there has been no recurrence of HCC despite cessation of sorafenib 9,11…”
Section: Discussionmentioning
confidence: 99%
“…Complete response to sorafenib has been reported previously in 40 case reports of patients with advanced HCC . Complete response to sorafenib in patients with bone metastasis is rare.…”
Section: Introductionmentioning
confidence: 85%
“…1,2 Complete response to sorafenib has been reported previously in 40 case reports of patients with advanced HCC. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Complete response to sorafenib in patients with bone metastasis is rare. In this case report, we describe CR to short-term sorafenib treatment in a patient with HCC and bone, lymph node, and peritoneal metastases.…”
Section: Introductionmentioning
confidence: 99%
“…One had portal vein tumor thrombus (PVTT) and the other developed portal vein thrombosis (PVT) during the treatment. Although both PVTT and PVT are regarded as negative prognostic factors for patients with HCC, previous studies have identified several patients with deteriorated portal flow who achieved complete remission (CR) while being treated with sorafenib (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). We hypothesized that the pathogenesis of disease may be similar in HCC patients who achieve CR and those who experience liver failure while on sorafenib.…”
Section: Introductionmentioning
confidence: 98%